Dimensional Clinical Personality Inventory 2: antecedents, development, and future improvements - Carvalho, Lucas Francisco de; Pianowski, Giselle (Interação em Psicologia, 2021)
Personality disorders (PDs) are characterized by impairments in the self and interpersonal relationships. People diagnosed with PD present distress in several areas of life. The prevalence of these disorders is 13% in Western countries and around 7% in Brazil. Despite the adverse outcomes related to PDs and its prevalence, these disorders tend to be undertreated in Brazil. One possible explanation is the lack of assessment scales to measure PDs typical traits. To fulfill this gap and improve mental health care in Brazil, the Dimensional Clinical Personality Inventory 2 (IDCP-2) was developed, an assessment tool that follows international guidelines and takes into account for the Brazilian reality. This paper aimed to present the main characteristics of IDCP-2, including its antecedents, development, theoretical and empirical foundations, as well as definitions of its 12 dimensions distributed in 47 factors. We discussed ongoing clinical research, limitations, and future improvements of the IDCP-2. Although IDCP-2 helps in fulfill the gap regarding PDs assessment in Brazil, efforts for the continuity of research focused on the PDs traits assessment is more than desirable, necessary for the advance of the mental health research area in the country.